2021
DOI: 10.36660/ijcs.20200087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Brazilian Cardioprotective Nutritional Program on the Quality of Life of Atherosclerotic Disease Patients

Abstract: Cardiovascular diseases (CVD) accounted for 45% of deaths in the world in 2015, causing a great impact on statistics. 1 In Brazil, mortality rates from diseases of the circulatory system are also high and represented 28% of deaths in 2017. 2 Therefore, CVD is considered a major public health problem. Most of the recorded deaths caused by CVD would be preventable if patients followed the prescribed medical treatment and controlled risk factors, including inadequate diet, smoking, obesity, physical inactivity, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The results indicated that the DICA-BR was effective in reducing LDL-C and improving quality of life in the intervention group. 5 Brazilian cardioprotective diet guidelines have been developed to encourage healthy eating practices, and this diet model is very effective because it values, recognizes, and considers the regional eating habits of the Brazilian population in its strategy to protect cardiovascular health. However, global research is needed to improve our understanding of LDL-cholesterol and determine treatment gaps in this persistent worldwide threat to health.…”
mentioning
confidence: 99%
“…The results indicated that the DICA-BR was effective in reducing LDL-C and improving quality of life in the intervention group. 5 Brazilian cardioprotective diet guidelines have been developed to encourage healthy eating practices, and this diet model is very effective because it values, recognizes, and considers the regional eating habits of the Brazilian population in its strategy to protect cardiovascular health. However, global research is needed to improve our understanding of LDL-cholesterol and determine treatment gaps in this persistent worldwide threat to health.…”
mentioning
confidence: 99%